Records of the Geological Society of London (as filmed by the AJCP) [M1682] - Geological Society of London; Murchison, Roderick Impey, Sir, 1792-1871.; National Library of Australia; Australian Joint Copying Project; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Selections of correspondence, maps and drawings relating to Australia and New Zealand in the archives of the Geological Society of London, which was founded in 1807. The main group comprises correspondence of Sir Roderick Murchison, President of the Society in 1831-33 and 1841-43, and includes letters of Sir Henry Barkly, W.B. Clarke, Sir John Franklin, J. Hector, P.P. King and C. Sturt.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M1682.
Also available online
Microfilm copy of originals held by the Geological Society of London, Burlington House, Piccadilly, London.
Keywords: Murchison, Roderick Impey, -- Sir, -- 1792-1871 -- Correspondence; Geological Society of London -- Archives; Geology -- Societies, etc. -- Archives; Geology -- Australia; Geology -- New Zealand